The Link between Personality Types and Reading Comprehension Achievement of the Eleventh Grade Senior High School Students - Suci Ulin (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
The aims of this study were (1) to find out whether each type of personality types had any significant correlation to reading comprehension achievement of the eleventh grade students of SMA Muhammadiyah 1; 2) to find out whether each type of personality types influenced reading comprehension achievement, and (3) which type of personality that became the best predictor of reading comprehension achievement. The method of this research was correlational research. The population of this research was all of the active students of SMA Muhammadiyah 1 Palembang in the academic year of 2018-2019 with total number of 1.298 students. However, there were only 132 students involved as sample in this research taken by using convenience sampling method. The students’ personality type score was taken by distributing questionnaire by Golberg (1992), while the students’ reading comprehension achievement was obtained by conducting reading test. To answer the first problem, Pearson Product Moment Correlation Coefficient was employed. The result of this study showed that there was no significant correlation between each type of personality types and reading comprehension achievement. Since there was no significant correlation, further analyses were eliminated.